2022
DOI: 10.1109/access.2022.3154044
|View full text |Cite
|
Sign up to set email alerts
|

A New CNN-Based Method for Short-Term Forecasting of Electrical Energy Consumption in the Covid-19 Period: The Case of Turkey

Abstract: This study proposes a new convolutional neural network (CNN) method with an input-signal decomposition algorithm. With the proposed CNN architecture, hourly electricity consumption data for the Covid-19 period in Turkey were used as input data, and the short-term electricity consumption was forecasted. The input data were decomposed into its subcomponents using a signal decomposition process called Empirical Mode Decomposition (EMD). To extract the deep features, all input data were transformed into 2D feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Further, most of the researchers have used only one to three models only. For instance, [ 1 ] utilized a multi-input multi-output CNN model to forecast SARS-COV-2 cases in several countries, including Malaysia. Their findings suggested that the CNN model effectively identified local patterns in the data and produced accurate forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Further, most of the researchers have used only one to three models only. For instance, [ 1 ] utilized a multi-input multi-output CNN model to forecast SARS-COV-2 cases in several countries, including Malaysia. Their findings suggested that the CNN model effectively identified local patterns in the data and produced accurate forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…The application of CNNs in the detection, prediction, and analysis of COVID-19 has demonstrated remarkable potential. This section provides a comprehensive literature review of CNNs with a focus on their architecture, applications, challenges, and ethical considerations, specifically in the context of COVID-19 [ 5 , 6 , 10 , 32 , 101 ]. The convolutional layer is the core building block of a CNN and possesses considerable depth and complexity that enables it to learn the spatial hierarchies of features automatically and adaptively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study used the Bayesian framework to evaluate the impact of lockdown and social distancing on the spread of the pandemic in top-populated countries and found that the pandemic would significantly accelerate if lockdown policies were relaxed. [6,9,[17][18][19][20][21]38,43,45,87] compared the forecasting performance of various deep learning models, including LSTM, CNN, and CNN-LSTM, with traditional machine learning methods, such as SVR and LR. The research indicated that deep learning models, particularly LSTM-CNN, outperformed traditional models in forecasting, with the most precise prediction demonstrated by [33,71,108,144].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations